2021
DOI: 10.3390/min11030315
|View full text |Cite
|
Sign up to set email alerts
|

Strength Characteristics of Clay–Rubber Waste Mixtures in Low-Frequency Cyclic Triaxial Tests

Abstract: This paper presents the results of consolidated and undrained (CU) triaxial cyclic tests related to the influence of tire waste addition on the strength characteristics of two different soils from Southern Poland: unswelling kaolin and swelling red clay. The test procedure included the normally consolidated remolded specimens prepared from pure red clay (RC) and kaolin (K) and their mixtures with two different fractions of shredded rubber powder (P) and granulate (G) in 5%, 10%, and 25% mass proportions. All s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Many authors pay attention to the fact that the main factor influencing the resilient modulus of untreated granular soils is the stress level, inter alia [4,[9][10][11][12][13], both confining pressure and applied axial stress. This phenomenon was also stated in the case of cohesive soils [14][15][16][17]. In all cases, the resilient modulus increased significantly with the confining pressure and marginally with the repeated axial stress.…”
Section: Introductionsupporting
confidence: 63%
“…Many authors pay attention to the fact that the main factor influencing the resilient modulus of untreated granular soils is the stress level, inter alia [4,[9][10][11][12][13], both confining pressure and applied axial stress. This phenomenon was also stated in the case of cohesive soils [14][15][16][17]. In all cases, the resilient modulus increased significantly with the confining pressure and marginally with the repeated axial stress.…”
Section: Introductionsupporting
confidence: 63%
“…Based on the above analysis, it can be concluded that the increase in compaction enhances the shear stress [37]. (6) According to the comparison of the shear strength indices of soil samples under different working conditions, the influence of water content control on the c and φ is obviously greater than that of compaction degree control, and it is difficult to reach a compaction degree of 93% during soil preparation. Choosing compaction degree as the control index of the project in the actual process of the project will not only increase the construction difficulty of the project and affect the construction progress, but the required compaction machinery will further increase the construction cost and increase the project investment.…”
Section: Discussionmentioning
confidence: 99%
“…The specific steps of the direct shear test are as follows: 1 ⃝ First, Vaseline is applied to the inner wall of the ring cutter to ensure smooth demolding; 2 ⃝ red clay samples with different compaction degrees and moisture contents are prepared using the compaction method; 3 ⃝ the ring knife sample is placed in the shear box with a piece of permeable stone and wax paper placed on both sides to prevent moisture loss, and a fixed pin is inserted to temporarily prevent the relative displacement of the upper and lower boxes; 4 ⃝ the edge of the ring knife is moved upward, the top edge of the ring knife is aligned with the shallow groove on the top surface of the upper box, and a bulldozer plug is used to gently press it into the shear box, cover the box cover, and adjust the vertical and horizontal pressure gauges; 5 ⃝ the shear rate is adjusted to 0.800 mm/min, four sets of vertical pressures are set in the control system to 50 kPa, 100 kPa, 150 kPa, and 200 kPa, stopping when the shear deformation is set to 8 mm; and 6 ⃝ data are recorded.…”
Section: Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubber waste from car tires can be used for this purpose, according to the rule "end-of-life tires" (ELT). Each such new application requires research [18,24,50]. Among the tests performed, direct shear tests [6,28,45], unconfined compression tests or triaxial tests [1,18,46] dominate.…”
Section: Introductionmentioning
confidence: 99%